PENERAPAN PEMBELAJARAN STEM-PROBLEM/BASED LEARNING BERBASIS LESSON STUDY DALAM KURIKULUM MERDEKA - Wiwita, Risma; Handayani, Revi; Mayeni, Riska (STKIP Pesisir Selatan, 2025)
The management of innovative teaching that hones critical thinking, problem-solving skills, and cross-disciplinary knowledge is becoming increasingly large. This study aims to analyze the management of learning with Science, Technology, Engineering, Mathematics-Model Problem Based Learning (STEM-PBL) approach based on Lesson study in ICT learning. This research uses a qualitative case study approach. The data sources are students, classroom teachers, peers, lecturers and school principals through observation, interviews and focus group discussions. The results showed that the management of STEM-PBL learning starts from the Plan stage by analyzing lesson planning. Then the Do stage, observing the learning process in an open classroom: triggering questions to find problems, discussions to collect data to solve problems, and presentations. See the stages, the reflection results of learning management are student-centered but need to be improved, namely smaller groupings of students with different genders, clear instructions, individual worksheets and presentations for all groups. It is concluded that STEM-PBL learning management is effective in improving student-centered learning activities. The findings provide valuable knowledge for educators and policy makers to improve the quality of learning through STEM-PBL approach and lesson study activities.